On the crossroads of interdisciplinary medicine in amyloidosis – study protocol for a single-center interdisciplinary registry study - Helena Pernice; Gina Barzen; Jakub Piwowarski; Harisa Muratovic-Colic; Anne Pankow; Vera von Landenberg-Roberg; Stephan Bohl; Eva Schrezenmeier; Paul J. Wetzel; Nicolas W. Wieder; Gunnar Fiß; Elisabeth Blüthner; et al. (PLoS ONE, 2026)
Background Systemic amyloidosis comprises a heterogeneous group of rare diseases characterised by extracellular deposition of misfolded protein fibrils, leading to progressive organ dysfunction. Due to the variability in clinical presentation and course, collection of system-specific and longitudinal data is essential for understanding disease progression, treatment response and patient outcomes. At the Amyloidosis Center Charité Berlin (ACCB), a prospective amyloidosis registry has been established to systematically collect clinical, laboratory, imaging and patient-reported data with the aim of improving the characterization of the diseases and facilitating translational research. Methods This is a single-center prospective registry study that enrols patients diagnosed with systemic amyloidosis. The registry includes demographic data, multidisciplinary clinical phenotyping, biomarkers, biobanking, genetic information, imaging studies, and patient reported outcomes. Here, we describe the standardised protocol for diagnostic workup, baseline and longitudinal data collection, and disease-specific follow-up algorithms. Data will be collected digitally in interoperable data formats to ensure shareability in accordance with GDPR-policies. Discussion This registry will serve as a resource for characterizing amyloidosis as a rare disease model in a real-world setting and identifying patterns in disease progression and treatment efficacy. By prospectively collecting high-quality longitudinal data, the study aims to generate insights that can inform clinical decision-making, improve risk stratification and support future intervention studies. In addition, the registry enables collaboration in the discovery of biomarkers and new therapeutic approaches. Ongoing analysis of this cohort will provide a basis for the further development of personalised treatment strategies and the improvement of patient care. Ethics and dissemination Ethical approval was given by the local ethic committee. Dissemination of data in publications with different scientific observational and correlational questions is planned. Clinical trial registration : DRKS00032002